Tribocorrosion behavior of bio-functionalized highly porous titanium - Toptan, Fatih (2017)
Titanium and its alloys are widely used in orthopedic and dental implants, however, some major clinical concerns such as poor wear resistance, lack of bioactivity, and bone resorption due to stress shielding are yet to be overcome. In order to improve these drawbacks, highly porous Ti samples having functionalized surfaces were developed by powder metallurgy with space holder technique followed by anodic treatment. Tribocorrosion tests were performed in 9 g/L NaCl solution using a unidirectional pin-on-disc tribometer under 3 N normal load, 1 Hz frequency and 4 mm track diameter. Open circuit potential (OCP) was measured before, during and after sliding. Worn surfaces investigated by field emission gun scanning electron microscope (FEG-SEM) equipped with energy dispersive X-ray spectroscopy (EDS). Results suggested bio-functionalized highly porous samples presented lower tendency to corrosion under sliding against zirconia pin, mainly due to the load carrying effect given by the hard protruded oxide surfaces formed by the anodic treatment.